2017
DOI: 10.1177/1538574417702777
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Congenital External Carotid-Jugular Fistula: Case Report and Review of the Literature

Abstract: Congenital vascular malformation (CVM) between the external carotid artery and the internal jugular vein is a rare disease, it originates as a consequence of arrested development during various stages of embryogenesis. The natural history of CMVs is progressive growth, it can remain clinically silent until it progresses causing local swelling accompanied by symptoms and signs of arteriovenous shunting, mass effect, ischemic insult with ulceration of skin or bleeding. In literature only few cases of CMVs have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…Pulsatile mass swelling is the main clinical manifestation. However, carotid-jugular fistulas are potentially dangerous, because they may cause serious complications of cardiac failure, rupture, thromboembolism, or cerebral ischemia (5), like hemiparesis in our case.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Pulsatile mass swelling is the main clinical manifestation. However, carotid-jugular fistulas are potentially dangerous, because they may cause serious complications of cardiac failure, rupture, thromboembolism, or cerebral ischemia (5), like hemiparesis in our case.…”
Section: Discussionmentioning
confidence: 81%
“…For its rarity, neither appropriate procedural standards or definitive surgical techniques have yet been established to treat congenital internal carotid-jugular fistulas. Operative ligations, detachable balloons, coiling, and stenting were all reported as treatment options for carotid-jugular fistulas (1, 4, 5). Operative ligation was not appropriate for our case, because of its location in the cranio-cervical region.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of developmental vascular anomalies in general population are seen in about 0.05%-0.25%, however agenesis of the IJV is rarely encountered and confirmed [2]. Different IJV abnormalities have been reported in scientific literature: partial or complete duplication [8], [9], [10], [11], [12], stenosis, complete occlusion, distortions, and intraluminal structures, such as membranes, webs, and inverted valves [13], [14], congenital external carotid artery-IJV fistula [15], congenital aneurysm [16], and fenestration [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that congenital arteriovenous fistulas located in the head and neck are usually unilateral. [4] A congenital arteriovenous fistula is a benign lesion in pathological morphology, but it has a malignant tendency to grow rapidly in clinical practice and must be monitored. According to the size and location of the fistula, a congenital arteriovenous fistula can be divided into three categories by pathology.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormal traffic branches are called fistulas. [3,4] In this report, we present a case of a congenital carotid-jugular (CJ) fistula in a fetus; the pregnant woman experienced termination of the pregnancy at 27 weeks, underwent induction surgery and the diagnosis was postoperatively confirmed as CJ fistula and left ear microtia. Fetal CJ fistula is an extremely rare vascular lesion.…”
Section: Introductionmentioning
confidence: 99%